Botulinum toxin A during pregnancy: a survey of treating physicians. Issue 1 (16th December 2005) - Morgan, J C; Iyer, S S; Moser, E T; Singer, C; Sethi, K D
Abstract : Botulinum toxin A (btxA) is widely used for cosmetic purposes, headaches, dystonia, spasticity, pain and other on and off label uses. Despite the widespread use of btxA in women of childbearing potential, there are few data on the effects of this drug on pregnant women and the fetus. The goal of this study was to survey physicians who use btxA, to determine their experience with pregnant women. We surveyed 900 physicians who used commercially available btxA. The questionnaire asked treating physicians if they had knowingly or unknowingly injected pregnant women and what was the outcome of each pregnancy. In total, 396 physicians (44%) returned questionnaires, of whom only 12 physicians reported injecting pregnant women with btxA. Sixteen pregnant women were injected, mostly in the first trimester, and only one patient, who had prior spontaneous abortions, suffered a miscarriage. Another woman had a therapeutic abortion. All other pregnancies went to term and there were no fetal malformations. Based on this limited survey of treating physicians in the USA, btxA appears to be relatively safe for both expectant mother and fetus. We need further data, however, and we would recommend that physicians and patients carefully consider the risks and benefits before using btxA in pregnant women.